2021
DOI: 10.1002/1878-0261.13036
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting of miR‐126‐3p and miR‐221‐3p inhibits PIK3R2 and PTEN, reducing lung cancer growth and metastasis by blocking AKT and CXCR4 signalling

Abstract: Co-targeting of miR-126-3p and miR-221-3p inhibits PIK3R2 and PTEN, reducing lung cancer growth and metastasis by blocking AKT and CXCR4 signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…According to a study by di Paolo et al, miR-221-3p inhibition combined with miR-126-3p augmentation induced tumour apoptosis [ 60 ]. This method was also well tolerated by normal cells [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study by di Paolo et al, miR-221-3p inhibition combined with miR-126-3p augmentation induced tumour apoptosis [ 60 ]. This method was also well tolerated by normal cells [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The miR-221/222 cluster was found to be overexpressed in the NSCLC [ 40 , 60 ]. MiR-221’s increased expression has been linked to a worse prognosis in lung cancer patients [ 60 ] and could serve as a prognostic tool [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 Interestingly, miR-221-3p was highly expressed in lung cancer, and the inhibition of miR-221-3p expression reduced the growth and metastasis of lung cancer. 51 Exosomal miR-10b-5p not only promoted the progression of glioma and gastric cancer, 52 , 53 but also played an important role in the early diagnosis of liver cancer and NSCLC, 54 , 55 especially lung adenocarcinoma. 56 All these previous studies suggest that the above miRNAs may be involved in exosomal EGFR-mediated EMT induced by HPV-16 E7 oncoprotein in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that high levels of miR-17 by targeting LKB1 identify NSCLC patients who are eligible for metabolic therapeutic strategy because they show sensitivity to energetic stress condition [ 12 ]. Moreover, the simultaneous modulation of miR-126-3p and miR-221-3p inhibits the phosphatase and tensin homolog (PTEN) and the phosphoinositide-3-kinase receptor 2 (PI3KR2), thus reducing metastatic dissemination of lung cancer cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%